Association between Eosinophilic Esophagitis and Esophageal Food Impaction in the Pediatric Population. (October 2018) - Ettyreddy, Abhinav R.; Sink, Jacquelyn R.; Georg, Matthew W.; Kitsko, Dennis J.; Simons, Jeffrey P.
Objectives: (1) To describe the presentation, management, and outcomes associated with pediatric esophageal food impaction (EFI) at a single tertiary care institution. (2) To identify the key clinical features of pediatric EFI that are associated with a diagnosis of eosinophilic esophagitis (EoE). Study Design: Case series with chart review. Setting: Tertiary care children's hospital. Subjects and Methods: Thirty-five children <18 years of age presenting with EFI between November 1, 2006, and October 31, 2013, were included. Presenting symptoms, medical history, biopsy results, endoscopic findings, and underlying etiology were examined. Fisher exact test, t tests, and logistic regression were used to compare between patients with and without EoE. Results: Thirty-five patients had isolated EFI and were included in the study. EoE accounted for 74% (n = 26) of pediatric EFI, with the remaining cases being attributed to neurologic impairment (n = 5, 15%), prior surgeries (n = 1, 3%), reflux esophagitis (n = 1, 3%), or unknown etiologies (n = 2, 6%). EFI was the initial manifestation of EoE in 81% (n = 21) of patients. The most common presenting symptoms were dysphagia (n = 34), choking (n = 26), and vomiting (n = 23). Linear furrowing was the only endoscopic finding that was significantly associated with EoE ( P < .001). Conclusion: Most esophageal food impactions in the pediatric population are associated with an underlying diagnosis of EoE and are often the initial manifestation of the disease. EoE must be considered in all pediatric patients with EFI; esophageal biopsies should be strongly considered in these patients at the time of endoscopic management of the EFI.